GLYCOSYLATED HEMOGLOBIN HBA1C AS A BIOMARKER FOR DIABETIC RETINOPATHY - FATIMA , S; ASHRAF , S; TAHIR , A; BATOOL , A; LATIF , I; AMEEN , I (Biological and Clinical Sciences Research Journal, 2024)
: Diabetes Mellitus (DM) is a long-term metabolic disorder marked by hyperglycemia. Diabetes may lead to various complications like retinopathy. Diabetic retinopathy is a microvascular disorder that may lead to vision loss. It was a hospital-based study to determine the prevalence of diabetic retinopathy in chronic diabetic patients. Patients who visited DHQ and Al Sheikh Hospital Sialkot with blurry or poor vision were taken as samples. The sample size for this study was 100. The demographic and medical history of patients were taken through a questionnaire. These patients were checked by an experienced ophthalmologist after the pupil dilation. After the proper examination, it was suggested that a patient have an HbA1c test to monitor diabetic control. The HbA1c test is one of the most effective techniques to monitor diabetic control. Out of the 100 patients, 60% were diagnosed with diabetic retinopathy. Out of these, 36% were diagnosed with non-proliferative diabetic retinopathy, and 24% were diagnosed with proliferative retinopathy. The results were quite alarming, as 60 out of 100 were suffering from diabetic retinopathy. This study provided the prevalence of diabetic retinopathy in the district of Sialkot. This study also helps to understand the severity of hyperglycemia that may lead to vision loss due to diabetic retinopathy.